If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3r + -6 = 6 + -1r Reorder the terms: -6 + 3r = 6 + -1r Solving -6 + 3r = 6 + -1r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add 'r' to each side of the equation. -6 + 3r + r = 6 + -1r + r Combine like terms: 3r + r = 4r -6 + 4r = 6 + -1r + r Combine like terms: -1r + r = 0 -6 + 4r = 6 + 0 -6 + 4r = 6 Add '6' to each side of the equation. -6 + 6 + 4r = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 4r = 6 + 6 4r = 6 + 6 Combine like terms: 6 + 6 = 12 4r = 12 Divide each side by '4'. r = 3 Simplifying r = 3
| 3000/450 | | -.15x=60 | | -26=x/4=9 | | K^2-10k-30=0 | | g+4g-3=12 | | -2v+1+2v=-7+v | | -26=x/4 | | -(x-4)=2x-7 | | -16+19q=20q | | (-2/3)x=-4/3 | | 2c+-3c=2 | | -(x+3)=9 | | 2x=19/5=3 | | 4m-3-4n=11 | | -15c+-10c+-10=-10 | | 8+6p=8+6p | | y-10=29 | | 8x-5x=30 | | 8/24=2/n | | 3(k+13)-17=-2 | | n=5p+28+4 | | 3(z+3)=7+3z-6z | | -2(2k-5)=10 | | -19=13-8y | | 3f-8=10f+9-8f | | y^4-3y^2-2y=0 | | n^2-34n+64=0 | | 2x^5+6x^4-4x^2=0 | | 1/4x-3/5=1 | | 8.1=5n-6.4 | | 6py/-5y | | -11w+w=-10 |